Konstitusi dan Kekosongan Regulasi AI: Tantangan Bagi Perlindungan Hak Asasi Manusia di Indonesia - cindy santika (Jurnal Kedaulatan Hukum, 2025)
The advancement of artificial intelligence (AI) technology has posed serious challenges to the protection of human rights in Indonesia. Although Articles 28A to 28J of the 1945 Constitution guarantee constitutional rights such as privacy, justice, and non-discriminatory treatment, there is currently no specific and comprehensive regulation governing the use and governance of AI. This regulatory gap opens the door to systematic yet invisible civil rights violations, such as algorithmic discrimination, breaches of personal data, and the lack of legal accountability for decisions made by AI systems. This research employs a normative-juridical approach by examining national legal provisions and comparing them with international legal frameworks, such as the European Union’s Artificial Intelligence Act and Canada’s Artificial Intelligence and Data Act. The findings indicate that Indonesia is not yet normatively prepared to anticipate the impacts of AI on human rights. Therefore, there is an urgent need for AI regulation that is grounded in constitutional values, technological ethics, and the principle of accountability, to ensure that digital innovation does not erode citizens’ fundamental rights, but rather supports the rule of law and democracy in the era of technological transformation.